The Algal Polysaccharide Ulvan and Carotenoid Astaxanthin Both Positively Modulate Gut Microbiota in Mice - Kunal Pratap; Marwan E. Majzoub; Aya C. Taki; Socorro Miranda Hernandez; Marie Magnusson; Christopher R. K. Glasson; Rocky de Nys; Torsten Thomas; Andreas L. Lopata; Sandip D. Kamath (Foods, 2022)
The intestinal microbial community (microbiota) is dynamic and variable amongst individuals and plays an essential part in gut health and homeostasis. Dietary components can modulate the structure of the gut microbiota. In recent years, substantial efforts have been made to find novel dietary components with positive effects on the gut microbial community structure. Natural algal polysaccharides and carotenoids have been reported to possess various functions of biological relevance and their impact on the gut microbiota is currently a topic of interest. This study, therefore, reports the effect of the sulfated polysaccharide ulvan and the carotenoid astaxanthin extracted and purified from the aquacultured marine green macroalgae Ulva ohnoi and freshwater green microalgae Haematococcus pluvialis, respectively, on the temporal development of the murine gut microbiota. Significant changes with the increase in the bacterial classes Bacteroidia, Bacilli, Clostridia, and Verrucomicrobia were observed after feeding the mice with ulvan and astaxanthin. Duration of the treatments had a more substantial effect on the bacterial community structure than the type of treatment. Our findings highlight the potential of ulvan and astaxanthin to mediate aspects of host-microbe symbiosis in the gut, and if incorporated into the diet, these could assist positively in improving disease conditions associated with gut health.